STUDI KERAPATAN MANGROVE DAN PERUBAHAN GARIS PANTAI TAHUN 1989-2018 DI PESISIR PROVINSI JAMBI - Achmad, Eva; Nursanti, Nursanti; Marwoto, Marwoto; Fazriyas, Fazriyas; Jayanti, Dwi Putri; Marwoto (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2020)
The density of mangrove cover is one of the factors that influence changes in shoreline both accretion and abrasion. This study aims to determine the effect of changes in density of mangrove cover on shoreline changes in 1989-2018 in the Coastal Province of Jambi. The method used is the interpretation of Landsat satellite images in 1989, 2000 and 2018 using NDVI (Normalized Difference Vegetation Index) and overlaying images to see shoreline changes and DSAS (Digital Shoreline Analysis System) to calculate the area of change. The results showed that there had been a change in shoreline both accretion and abrasion in several locations that had different mangrove densities in the period 1989-2018. The results showed that accretion occured in 6 locations with an average change of Kota Sebrang 771 m, Tungkal Ilir 240.65 m, Kuala Betara 153.73 m, Mendahara 167.78 m, Kuala Jambi 169.35 m and Nipah 57.3 m, while abrasion occurs at 2 locations with an average change in Sabak Timur -41.8 m and Sadu -36.55 m. Where in the 6 locations that had accretion, mangrove density dominantly was in a close-densed and moderate state and only a few are in a low-densed condition. Meanwhile, the 2 locations that had abrasion were in a moderate state and have a low density mangrove forest.